2022
DOI: 10.1177/20503121221105993
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of central obesity and associated factors among adults working in government offices in Bedele town, Buno Bedele zone, Southwest Ethiopia

Abstract: Objective: Central obesity is an emerging public health problem globally and an independent risk factor for heart, blood vessels, and metabolic disorder. This study aimed to assess the central obesity and associated factors among adults working in government offices in Bedele town, Southwest Ethiopia, 2021. Methods: An institutional survey was conducted among randomly selected government offices. Anthropometric measurements were carried out. Face-to-face interview using standard questionnaires were also used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
2
1
2
Order By: Relevance
“…There are con icting links between alcohol consumption and obesity. This study, however, demonstrated statistically signi cant positive associations between alcohol use and central obesity, consistent with the ndings of previous studies [21,23,37,45,46]. Alcohol is considered a nontrivial energy source that may lead to a positive energy balance, weight gain, and eventually the emergence of obesity among drinkers [21,42,47,48].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are con icting links between alcohol consumption and obesity. This study, however, demonstrated statistically signi cant positive associations between alcohol use and central obesity, consistent with the ndings of previous studies [21,23,37,45,46]. Alcohol is considered a nontrivial energy source that may lead to a positive energy balance, weight gain, and eventually the emergence of obesity among drinkers [21,42,47,48].…”
Section: Discussionsupporting
confidence: 90%
“…The overall magnitude of central obesity in this study was lower than the prevalence of central obesity among public service workers in Bedele town [23], the pooled prevalence of central obesity among adult populations in Ethiopia [32], and the prevalence of central obesity among health service providers and public transportation workers in Nigeria and Peru [20,33].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Both hyperuricemia and T2DM were metabolic syndromes. Metabolic disorders were quite associated with central obesity, insulin resistance, hypertension and hyperlipemia in previous studies 20 22 .…”
Section: Discussionmentioning
confidence: 88%
“…5 Masa başı çalışanlarda hareketsiz yaşam tarzının kötü beslenme alışkanlıklarına neden olarak, obezite başta olmak üzere, çeşitli sağlık sorunlarına neden olduğu belirtilmektedir. 6 Yetkililer tarafından bu duruma karşı önlem alınmadığı takdirde işyerindeki verimliliğin büyük oranda azalacağı vurgulanmaktadır. 7 Genel literatürde masa başı çalışanlarda hareketsiz yaşam tarzına bağlı kötü beslenme alışkanlıkları olduğu vurgulanmaktadır.…”
Section: Introductionunclassified